Fiscal Consolidation in Reformed and Unreformed Labour Markets: A Look at EU Countries - Alessandro Turrini (Institute for the Study of Labor (IZA), 2012)
This paper estimates the impact of fiscal consolidation on unemployment and job market flows across EU countries using a recent database of consolidation episodes built on the basis of a narrative approach (Devries et al., 2011). Results show that the impact of fiscal consolidation on cyclical unemployment is temporary and significant mostly for expenditure measures. As expected, the impact of fiscal policy shocks on job separation rates is much stronger in low-EPL countries, while high-EPL countries suffer from a stronger reduction in the rate at which new jobs are created. Since a reduced job-finding rate corresponds to a longer average duration of unemployment spells, fiscal policy shocks also tend to have a stronger impact on long-term unemployment if EPL is stricter. Results are broadly confirmed when using top-down fiscal consolidation measures based on adjusting budgetary data for the cycle.
Keywords: E62; J63; J65; 330; fiscal consolidation; unemployment; job market flows; employment protection legislation; labour market reforms; Haushaltskonsolidierung; Beschäftigungseffekt; Arbeitsmarktflexibilität; Arbeitnehmerschutz; EU-Staaten